Klub glavnykh redaktorov . Klub glavnykh redaktorov . Club of the Editors-in-Chief . Клуб главных редакторов - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing professional ethics of journalists and the political orientation of newspapers during the political crisis. Featured in the program: Golembiovskii, Igor' Nestorovich (Journalist); IAkovlev, Egor (Journalist); Gusev, Pavel (Journalist); Chikin, Valentin (Journalist); Seleznev, Gennadii (Journalist); IAkovenko, Igor' (Journalist); Prokhanov, Aleksandr (Journalist) Дискуссия о профессиональной этике журналистов и политической направленности газет во время политического кризиса. В программе участвуют: Голембиовский, Игорь Несторович (Журналист); Яковлев, Егор (Журналист); Гусев, Павел (Журналист); Чикин, Валентин (Журналист); Селезнев, Геннадий (Журналист); Яковенко, Игорь (Журналист); Проханов, Александр (Журналист)